Methods of Analysis the Motives for Legal Tax Behavior - M. R. Pinskaya; A. V. Tikhonova (Финансы: теория и практика)
The paper is devoted to improving the methodology for conducting laboratory experiments to study the actions of taxpayers. We note that the use of standard economic methods is not enough to study citizens’ behavioral motives (in particular, the desire to evade their duties). The authors analyzed experimental methods of studying tax evasion, carried out their comparative characteristics and identified the problems of their implementation in practice. Based on the analysis of the results of previous experiments, we proved that involving students as interviewers enables us to identify and evaluate the behaviour trends of taxpayers. The research methodology is based on the use of tools and methods of comparative analysis, tabular and graphical methods of data visualization. In particular, the comparative characteristics of the form factor surveys (vignette with one profile, vignette with a double profile, single-profile association, conjugate profile, conjugate paired profile) made it possible to identify as a priority for use in laboratory tax experiments the conjugate paired profile in the form of a survey. In the resulting part of the paper, we presented the disadvantages of laboratory experiments and suggested possible options for their solution, which is an element of scientific novelty and the significance of the research’ results.